PROBLEMATIKA DAN EFEK NEGATIF PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Khotibul Umam; Lailiyatul Maulidah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Covid-19 pandemic has had a tremendous impact on the world of education. It has been almost a year that we have implemented online learning to reduce activities outside the home and our support for government programs to break the chain of spreading the Covid-19 virus. But in fact, the application of online learning is not as easy as imagined. This study aims to reveal the problems and negative effects of the application of online learning during the Covid-19 pandemic. The technique used is a literature review by collecting several previous articles that are relevant to this research. The results of this study indicate that the main problems in online learning are limited facilities such as Internet networks and electronic devices, lack of adequate human resources, students' lack of awareness of education and lack of support from parents of students. While the negative effects that arise from online learning are reduced motivation and activeness of students, loss of social life in students, stress for parents and students and the growth of maladaptive attitudes in students such as laziness and cheating.